Oxidative stress in menopause and gynecologic cancer - Pacheco Romero, José (2015)
The climacteric is the phase when a woman passes from the reproductive stage to the non-reproductive, and menopause occurs at about age 51. Oxidative stress represents imbalance between production of reactive oxygen (unpaired oxygen) and the biologic system capacity to rapidly detoxify from free radicals or repair the resulting injury. Aging and the climacteric and menopause have been related to oxidative stress - including free radicals and reactive oxygen species increase- linked to acute (neurovegetative symptoms) and chronic (metabolic syndrome, cardiovascular disease, hypertension, osteoporosis, cancer) symptomatology of this woman’s phase, also dependent from estrogen depletion. In this article we review recent research on gynecologic oxidation-neoplastic degeneration in the climacteric woman, emphasizing advances on the importance of natural antioxidants in health and cancer prevention, antioxidants that we obtain in our diet, pending at this time the real usefulness of vitamin supplements as antitumor antioxidant agents.